Swot Analysis of Marketing Strategies for Wood Craftsmen "Jati Makmur" in Teleng Hamlet, Maguwan Village - Renny Indryana; Riani Nur Aini; Risma Yuliani; Silvia Marlinda Rohmawati (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Sales is the most important activity because it is related to income which is the goal to determine the survival of a business that has been run. In entrepreneurship, an entrepreneur must be able to think creatively and innovatively in running his business. So this study aims to analyze marketing strategies and marketing constraints to increase the number of sales of the Makmur Teak Wood Craftsman Business in Maguwan Village, Sambit District, Ponorogo Regency, East Java. This research is a type of descriptive qualitative research. The data collection method is by means of observation and interviews. To analyze this research using the SWOT analysis method. In this business using marketing that is still word of mouth. In this study using SWOT analysis to analyze the business of "Jati Makmur" wood craftsmen, namely the strengths (strenghts) in their marketing, namely being able to respond quickly to customer requests, weaknesses (weaknesses) marketing that does not have stock items and the ordering process can take a long time, opportunities) this marketing has a big enough opportunity because in the Teleng area there is only one furniture, especially if it is sold in applications that are often visited by many people for home needs, as for marketing threats, namely slow business growth, increasing bargaining power from buyers, and business places in remote places.